A novel root-to-shoot stomatal response to very high CO2 levels in the soil: electrical, hydraulic and biochemical signalling - Lake, Janice A.; Walker, Heather J.; Cameron, Duncan D.; Lomax, Barry H. (Wiley, 2017)
Investigations were undertaken in the context of the potential environmental impact of Carbon Capture and Storage (CCS) transportation in the form of a hypothetical leak of extreme levels of CO2 into the soil environment and subsequent effects on plant physiology. Laboratory studies using purpose built soil chambers, separating and isolating the soil and aerial environments, were used to introduce high levels of CO2 gas exclusively into the rhizosphere. CO2 concentrations greater than 32% in the isolated soil environment revealed a previously unknown whole plant stomatal response. Time course measurements of stomatal conductance, leaf temperature and leaf abscisic acid show strong coupling between all three variables over a specific period (3 hrs following CO2 gassing) occurring as a result of CO2-specific detection by roots. The coupling of gs and ABA subsequently breaks down resulting in a rapid and complete loss of turgor in the shoot. Root access to water is severely restricted as evidenced by the inability to counter turgor loss, however the plant regains some turgor over time. Recovery of full turgor is not achieved over the longer term. Results suggest an immediate perception and whole plant response as changes in measured parameters (leaf temperature, gs and ABA) occur in the shoot, but the response is solely due to detection of very high CO2 concentration at the root/soil interface which results in loss of stomatal regulation and disruption to control over water uptake.